Clinical strains of Streptococcus agalactiae carry two different variants of pathogenicity island XII - Kuleshevich, Eugenia; Ferretti, Joseph; Santos Sanches, Ilda; Balasubramanian, Natesan; Spellerberg, Barbara; Efstratiou, Androulla; Kriz, Paula; Grabovskaya, Kornelia; Arjanova, Olga; Savitcheva, Alevtina; Shevchenko, Valentin; Rysev, Anton; et al. (Folia microbiologica, 2017)
Streptococcus agalactiae or Group B streptococci (GBS) are a common cause of serious diseases of newborns and adults. GBS pathogenicity largely depends on genes located on the accessory genome including several pathogenicity islands (PAI). The present paper is focused on the structure and molecular epidemiological analysis of one of the GBS pathogenicity islands-the pathogenicity island PAI XII (Glaser et al. Mol Microbiol 45(6):1499-1513, 2002). This PAI was found to be composed of three different mobile genetic elements: a composite transposon (PAI-C), a genomic islet (PAI-B), and a pathogenicity island associated with gene sspB1 (PAI-A). PAI-A in GBS has a homolog--PAI-A1 with similar, but a different genetic constellation. PCR-based analysis of GBS collections from different countries revealed that a strains lineage with PAI-A is less common than PAI-A1 and was determined to be present only among the strains obtained from Russia. Our results suggest that PAI-A and PAI-A1 have the same progenitor, which evolved independently and appeared in the GBS genome as separate genetic events. Results of this study reflect specific geographical distribution of the GBS strains with the mobile genetic element under study.
Keywords: molekulární evoluce; Humans; Sequence Analysis, DNA; Genomic Islands; Genes, Bacterial; Evolution, Molecular; Genotype; lidé; Streptococcus agalactiae; genomové ostrovy; výpočetní biologie; streptokokové infekce; Gene Order; Streptococcal Infections; sekvenční analýza DNA; Computational Biology; pořadí genů; bakteriální geny; genotyp; Global Health; celosvětové zdraví